Discovery and 3D imaging of a novel ΔNp63-expressing basal cell type in human pancreatic ducts with implications in disease. Issue 10 (30th July 2021) - Martens, Sandrina; Coolens, Katarina; Van Bulck, Mathias; Arsenijevic, Tatjana; Casamitjana, Joan; Fernandez Ruiz, Angel; El Kaoutari, Abdessamad; Martinez de Villareal, Jaime; Madhloum, Hediel; Esni, Farzad; Heremans, Yves; Leuckx, Gunter; et al.
Abstract : Objective: The aggressive basal-like molecular subtype of pancreatic ductal adenocarcinoma (PDAC) harbours a ΔNp63 (p40) gene expression signature reminiscent of a basal cell type. Distinct from other epithelia with basal tumours, ΔNp63 + basal cells reportedly do not exist in the normal pancreas. Design: We evaluated ΔNp63 expression in human pancreas, chronic pancreatitis (CP) and PDAC. We further studied in depth the non-cancerous tissue and developed a three-dimensional (3D) imaging protocol (FLIP-IT, Fluorescence Light sheet microscopic Imaging of Paraffin-embedded or Intact Tissue) to study formalin-fixed paraffin-embedded samples at single cell resolution. Pertinent mouse models and HPDE cells were analysed. Results: In normal human pancreas, rare ΔNp63 + cells exist in ducts while their prevalence increases in CP and in a subset of PDAC. In non-cancer tissue, ΔNp63 + cells are atypical KRT19 + duct cells that overall lack SOX9 expression while they do express canonical basal markers and pertain to a niche of cells expressing gastrointestinal stem cell markers. 3D views show that the basal cells anchor on the basal membrane of normal medium to large ducts while in CP they exist in multilayer dome-like structures. In mice, ΔNp63 is not found in adult pancreas nor in selected models of CP or PDAC, but it is induced in organoids from larger Sox9 low ducts. In HPDE, ΔNp63 supports a basal cell phenotype at the expense of a classical duct cell differentiation programme. Conclusion: In larger human pancreatic ducts, basal cells exist. ΔNp63 suppresses duct cell identity. These cells may play an important role in pancreatic disease, including PDAC ontogeny, but are not present in mouse models.